Galactooligosaccharide Treatment Alleviates DSS-Induced Colonic Inflammation in Caco-2 Cell Model - Roselli, Marianna; Maruszak, Aleksandra; Grimaldi, Roberta; Harthoorn, Lucien; Finamore, Alberto (Frontiers in Nutrition, 2022)
Biological activities of dietary bioactive polysaccharides have been largely explored. Studies on immunomodulating effects of oligosaccharides and polysaccharides have shown that they are able to modulate innate immunity. Prebiotics, are a class of poorly digested carbohydrates, that are mainly produced from dietary fibers, which are carbohydrate polymers with ten or more monomeric units as defined by the Codex Alimentarius Commission in 2009. Considering the capacity of prebiotics in reducing gut inflammation, the aim of this study was to investigate the anti-inflammatory activity of a galactooligosaccharide (Bimuno GOS) in an in vitro model of ulcerative colitis (UC)-like inflamed intestinal cells. Differentiated Caco-2 cells were exposed to 2 % dextran-sulphate-sodium salt (DSS) to induce inflammation, and then with different concentrations of Bimuno GOS (1-1000 μg/mL). Cell monolayer permeability, tight- and adherent junction protein distribution, pro-inflammatory cytokine secretion and NF-kB cascade were assessed. Bimuno GOS, at different concentrations, while not affecting cell monolayer permeability, was shown to counteract UC-like intestinal inflammatory responses and damages induced by DSS. Indeed Bimuno GOS was able to counteract the detrimental effects of DSS on cell permeability, determined by transepithelial electrical resistance, phenol red apparent permeability, and tight- and adherent junction protein distribution. Furthermore, Bimuno GOS inhibited DSS-induced NF-kB nuclear translocation and pro-inflammatory cytokine secretion. Further analyses showed that Bimuno GOS was able to revert the expression levels of most of the proteins involved in NF-kB cascade to control levels. Thus, the prebiotic Bimuno GOS can be a safe and effective way to modulate the gut inflammatory state through NF-kB pathway modulation, and could possibly further improve efficacy in inducing remission of UC.